Survey of the entomofauna associated with potato varieties during two crop seasons - Grutzmacher, Anderson Dionei; Link, Dionisio (Pesquisa Agropecuaria Brasileira, 2000)
A survey of arthropods present in a potato (Solanum tuberosum L.) agroecossystem was conducted in Santa Maria, RS, Brazil, during 1989/90 field season. The objective of this research was to compare the entomofauna in different potato cultivars during the traditional and off-season time for potato growing. The experiment consisted of nine cultivars during the traditional season and ten cultivars during the off-season time. Insect samples were taken weekly with a sweep net (15 nets per sample). Coleoptera was the predominant insect order during the traditional potato growing season, and Diptera during the off-season. Epitrix sp. was quantitatively the most important in the traditional season, and Diabrotica speciosa (Germar) in the off-season, followed by Empoasca kraemeri Ross & Moore in both potato growing season. Greater number of insects was collected during the traditional season than off-season for growing potatoes. Insects preferred Bintje cultivar during the traditional season and Pomina cultivar during the off-season time. Sahael cultivar was the least preferred in both potato growing season. Eriopis connexa (Germar) and Geocoris sp. were the most abundant predator species in the traditional potato growing season. During the off-season, Cycloneda sanguinea (L.) was the predominant species in all cultivars.